PENGARUH LATIHAN REVERSE BODY LIFTS TERHADAP KEKUATAN OTOT PUNGGUNG ATLET KADET PUTRA GULAT RIAU - Denis Diva Jordan Lb. Batu; Zainur Zainur; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Based on the observations of research at PPLP Gulat Dispora Riau and the results of interviews with coach Yudha Setia Nugraha where the male cadet athletes of Riau wrestling aged 15-17 years have a deficiency which is influenced by one of the factors of physical condition, namely strength, where when carrying out leg attacks the strength of the back muscles not strong so that the opponent can anticipate by pressing his body down, wrestlers also find it difficult to lift the opponent that hit his body, and difficulty lifting the opponent's leg when standing. The title that the research examined was